PRODUKSI BAWANG MERAH (Allium ascalonicum L.) DENGAN PEMBERIAN TRICHOKOMPOS TERFORMULASI DAN KALIUM DI LAHAN GAMBUT RIMBO PANJANG KABUPATEN KAMPAR, RIAU - Herlina, Nofripa; Elsie, - (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2016)
The research aims to study the effect of the provision interaction Trichokompos of oil palm empty bunches (OPEB) formulated and potassium fertilizer, the main effect of both the growth and production and K nutrient uptake by plants red onion (Allium ascalonicum L.) on peat land. The study was conducted experimentally in the form of 4 x 3 factorial prepared using a completely randomized design (CRD). Trichokompos OPEB formulated as the first factor consisted of 4 levels (15, 20, 25 and 30 ton / ha) and potassium as the second factor consists of three levels (50, 100 and 150 kg KâO / ha). The observed parameters include the number of tillers, fresh weight of tuber per mÂ², K nutrient uptake and clump of dry weight tubers per sample red onion crop. The results showed that the 25 ton / ha Trichokompos OPEB formulated and 100 kg KâO / ha increased fresh weight of tuber per mÂ² until 1.7 times (71.3%), K uptake by 2.8 times (185%) and dry weight clump of tubers per sample by 2.5 times (154.5%) compared to the provision of 15 tons / ha at the same doses of potassium fertilizer (100 kg KâO / ha). Enhancement of doses Trichokompos OPEB formulated from 15 to 25 tonnes / ha increased fresh weight of tuber per mÂ², K uptake and dry weight of tuber per sample. Enhancement of doses to 30 tonnes / ha still affect the increase in all parameters observed. Enhancement of doses potassium from 50 to 100 and 150 kg KâO / ha did not affect all parameters observed.